2013
DOI: 10.1016/j.jpainsymman.2012.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Referral-to-Death Interval and Location of Death of Patients Referred to a Hospital-Based Specialist Palliative Care Service

Abstract: Longer referral-to-death interval was associated with death outside the hospital for patients enrolled in a hospital-based service. The study highlights the importance of early referral in predicting the last place of care and location of death of palliative care patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 46 publications
4
54
0
1
Order By: Relevance
“…The median length of referral from hospital to death at home was 35 days, and approximately 10 % of the patients died within 1 week. These findings are generally consistent with the existing literature, reporting that patients were referred to home hospice care at a late stage of cancer [4][5][6][7][8][9][10][11]. The fact that over 40 % of family members responded that the timing of referrals was late or too late suggests that the timing of referrals to home hospice care is likely to be delayed, and a strategy needs to be developed to improve this situation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The median length of referral from hospital to death at home was 35 days, and approximately 10 % of the patients died within 1 week. These findings are generally consistent with the existing literature, reporting that patients were referred to home hospice care at a late stage of cancer [4][5][6][7][8][9][10][11]. The fact that over 40 % of family members responded that the timing of referrals was late or too late suggests that the timing of referrals to home hospice care is likely to be delayed, and a strategy needs to be developed to improve this situation.…”
Section: Discussionsupporting
confidence: 88%
“…Multiple surveys from several countries, however, have consistently shown that physicians referred patients to hospice care services at the very latest stage of cancer: the median interval from referral to patient death ranged from 2 to 6 weeks and about 15 to 35 % of the patients died within a week after referral [4][5][6][7][8][9][10][11]. Some studies demonstrated that a shorter length of hospice enrollment was associated with an increased risk of major depressive disorder in family caregivers, less satisfaction with hospice care of family caregivers, and inadequate symptom management [9,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is however possible to broadly categorise the literature into those studies reporting exposure to hospital-based palliative care services and those reporting community or hospice-based services. Studies from the UK,16 17 the USA,18 19 Korea20 and Singapore21 report the median duration of HPC to range from 14.4 to 57 days and studies reporting CPC from Canada,22 Italy15 and Ireland7 report duration to range from 40 to 70 days. These studies provide useful context to the data reported here (20 days to HPC; 46 days CPC) and show the timing of referral to be consistent with that reported in the international literature.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to divide patients according to the timing of PC decisions and service usage by using time periods before death on clinical grounds and thus complying with most of the previous studies; however, the lack of strict recommendations on this timing makes comparison between previous studies and the present study somewhat difficult. Regarding the timing of the PC initiation, in two previous studies [15,17] early PC referral was defined as a referral to PC >30 days, whereas in the study by Alsirafy and co-workers [16] the timing of PC referrals were categorized as early (> 90 days before death), intermediate (30-90 days before death) and late (<30 days before death). In the study by Nieder and co-workers [18], three months before death was chosen as a time point to distinguish between an early and late PC.…”
Section: Resource Usementioning
confidence: 99%